Voltammetry in the absence of excess supporting electrolyte - ECE-DISP1 reactions: The electrochemical reduction of 2-nitrobromobenzene in acetonitrile solvent - Barnes, E; Wang, Y; Limon-Petersen, J; Belding, SR; Compton, R (2011)
The reduction of 2-nitrobromobenzene in acetonitrile has been studied in the presence and near absence of supporting electrolyte at a mercury hemispherical microelectrode. In the presence of a high concentration of tetra-n-butylammonium perchlorate, voltammetric studies over a wide range of voltage scan rates spanning the transition from convergent to linear diffusion confirms the reduction mechanism as DISP1, rather than ECE, as previously thought by the majority of earlier studies. A rate constant of approximately 23 s-1 at 298 K was inferred for the loss of bromide ion from the 2-nitrobromobenzene radical anion. In the presence of weak support, with concentration ratios of electrolyte to reactant of 5 and 0.5, the Nernst-Planck-Poisson system of equations were used to model the coupled diffusion-migration-reaction. It was found the both the mechanism of reaction and the derived homogeneous kinetics were unchanged in the near absence of supporting electrolyte. © 2011 Elsevier B.V. All rights reserved.